Tradisi Nyadran dan Kerukunan Umat Beragama di Makam Ki Sungkem Kabupaten Blitar - Kharisma Amanda Putri; Miftakhus Sifa' Bahrul Ulumiyah; Akhmad Najibul Khairi Syaie (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2022)
Abstract: The community of Jajar Village, Talun District, Blitar Regency, East Java Province is a plural society that then develops itself as a multicultural society through the nyadran ritual. This study seeks to examine the role of nyadran in shaping the concept of multiculturalism in the inter-religious life of the Jajar community and the existence of these rituals in the lives of their people. This research is a qualitative descriptive study with data collection through the process of observation, interviews, and literature review. Koentjoroningrat's religious concepts and autonomous multicultural theory were used to assist the analysis. The results of this study indicate that the nyadran ritual carried out by the Jajar people as a request for ancestral blessing, a mandatory tradition carried out by two religious groups (Islam and Hinduism), with mutually agreed terms, as well as a form of development of the concept of animism and worship of parwatarajadewa. The nyadran ritual in Jajar Village is also a subject as well as an object in realizing the life of an autonomous multicultural society. Keywords: Ki Sungkem, Nyadran, religious people